GUIDELINES ON UKRAINIAN HIGHER EDUCATION MODERNISATION THROUGH EDUCATIONAL ACHIEVEMENTS OF SOUTH KOREA - Nazarenko , Oleksandra (The Modern Higher Education Review, 2023)
Within the article, the author delves into an examination of higher education within the context of South Korea. This examination is grounded in an assessment of its legislative, organizational, and substantial dimensions of operation. The author proceeds to delineate the pivotal elements that have underpinned South Korea’s accomplishments in the realm of higher education, encompassing governmental strategies, educational investment, advances in scientific research, and the interplay of societal and cultural facets within the national framework. Through a comprehensive scrutiny of the South Korean model, the author accentuates pertinent issues that hold relevance for Ukrainian higher education during the backdrop of wartime conditions and the ensuing phase of post-war reconstruction. Furthermore, the article elucidates the potentialities inherent in assimilating the constructive lessons drawn from South Korea’s educational achievements and translating them into practical applications within the Ukrainian context. This endeavour takes into careful consideration the distinctive national attributes and the exigencies that society will encounter during the post-war epoch. The matter of adapting specific methodologies for the administration of higher education, notably pertaining to the collaboration between institutions of higher learning, the governmental apparatus, and industry stakeholders, is also unveiled. These approaches hold promise for Ukraine’s higher education modernisation, fostering a substantial enhancement of its research capabilities. By way of a comparative lens, the author brings to light the potential of harnessing South Korea’s higher education experience as a catalyst for the nation’s resurgence post-conflict and proffers corresponding recommendations.